Assessment of femoral access site hematoma formation incidence and risk factors among post cardiac catheterization patients in 2024 - Amal Ahmad Ibrahim Alshubaily; Asma Ahmad Ibrahim Alshubaily; Fawzia Ali Aziz Alzahrani; Rabab Ali Abdallah Alghamdi; Ibtisam Abdulkarim Aljohani; Rugaia Abdurahman Farg Al Sultan; Khadijah Hasan Ashoor Alsaiadi; Sayed Ameen Abobakor; Mohammad Abdullah Aljuhani; Fatimah Huzaym Wasel Aldajani; Sara Fahad Daifalla Alotaibi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: An invasive cardiovascular procedure's frequent and potentially seriouscomplication is hematoma formation at the femoral access site. Aims: To assess the incidence and risk factors of hematoma formation atfemoral access site among patients post cardiac catheterization. Design: Descriptive research design was used. Subject and setting: All available adult patients (200), aged 18-65 years old, from both sexes who were attend tocardiac Catheterization unit at Makkah Hospital, Saudi Arabia for a diagnostic procedures or interventional cardiaccatheterization within 6 months’ period. Tools: two tools were used (I) Patient interview questionnaire, and (II) riskfactors assessment list. Results: Incidence of femoral access hematoma formation over six months was (20%)percentage. Regarding medical data more than half of the studied patients had hypertension (61.5%), majority had ahistory of previous hospitalization (84.0%), large portion of them performed cardiac catheterization for diagnosticpurposes and were smokers (39.0%). Regarding the modifiable risk factors, obesity was the 29(14.5%), positionchange during compression31(15.5%),Numberof artery puncture (25%) Renal dysfunction 19(9.5%),Earlyambulation 27(13.5), Use of anticoagulant 17(8.5%). Regarding the non-modifiable risk factors were found among29(14.5%) of the studied patients who were advanced in age 29(14.5%) andmale gender was 27(13%) While, thenon-modifiable risk factors were 14.5 1.5 and 9.5% including advanced age and hypertension among male patients. Conclusion: There was A hematoma formation among patients after cardiac catheterization. There was correlationbetween medical data, modifiable risk factors & non-modifiable risk factors. Recommendations: Developing astandardizing protocol about hemostasis, sheath removal for providing education and training to healthcare providersto identifyandmanage suchriskfactors.